Analysis of Changes in Flavor Substances of Tomato Fruits in Different Ripening Stages by Headspace-Gas Chromatography-Ion Mobility Spectrometry - FU Xiaohui, SHI Lu, SUN Qingzhen, DONG Xiaoxing, PIAO Fengzhi, DU Nanshan (Shipin Kexue)
High performance liquid chromatography (HPLC) and headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) were employed to analyze the changes in volatile metabolites in wild-type Ailsa Craig tomato fruits in four ripening stages (mature green, breaker, light ripe and red ripe) at the metabolic and transcriptional levels. The results showed that the contents of citric acid, lycopene and β-carotene in tomato fruits increased with fruit ripening, while the contents of malic acid and β-cryptoxanthin decreased. Our analysis identified 81 volatile components across the four stages, the total amount of these compounds being in the decreasing order of red ripe > light ripe > breaker > mature green. Correlation analysis between 40 differential metabolites and quality indicators indicated that lycopene was positively correlated with the volatile metabolite 6-methyl-5-hepten-2-one. Furthermore, the expression of chlorophyll degradation-related gene (SlSGR1) and carotenoid synthesis-related gene (SlPSY1) reached their highest levels in the breaker stage, mirroring the trend observed for trans-2-hexenal. The expression of carotenoid synthesis-related genes (SlLCYb and SlBCH2) peaked in the red ripe stage, mirroring the trend of 6-methyl-5-hepten-2-one. We hypothesized that the regulation of genes related to carotenoid metabolism during ripening period may alter the flavor of tomato fruits. This study will contribute to a comprehensive understanding of the intrinsic mechanisms underlying tomato fruit ripening, and provide a new theoretical basis for the metabolic regulation of flavor during fruit ripening and the improvement of fruit quality.